2018
DOI: 10.1038/s41598-018-21155-w
|View full text |Cite|
|
Sign up to set email alerts
|

WDR1 is a novel EYA3 substrate and its dephosphorylation induces modifications of the cellular actin cytoskeleton

Abstract: Eyes absent (EYA) proteins are unusual proteins combining in a single polypeptide chain transactivation, threonine phosphatase, and tyrosine phosphatase activities. They play pivotal roles in organogenesis and are involved in a variety of physiological and pathological processes including innate immunity, DNA damage repair or cancer metastasis. The molecular targets of EYA tyrosine phosphatase activity are still elusive. Therefore, we sought to identify novel EYA substrates and also to obtain further insight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Recently, we have demonstrated that c-Src phosphorylates tyrosine residues of human EYA1 and EYA3 to control their nuclear and cytoskeletal localization [30]. We have also found that EYA1 and EYA3 are capable of autodephosphorylation [30]. These data indicate a potential implication of EYA tyrosine phosphorylation and autodephosphorylation in regulating physiological processes and contributing to pathological conditions.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, we have demonstrated that c-Src phosphorylates tyrosine residues of human EYA1 and EYA3 to control their nuclear and cytoskeletal localization [30]. We have also found that EYA1 and EYA3 are capable of autodephosphorylation [30]. These data indicate a potential implication of EYA tyrosine phosphorylation and autodephosphorylation in regulating physiological processes and contributing to pathological conditions.…”
Section: Introductionmentioning
confidence: 81%
“…For example, c-Src activation has been reported to generate more than 50% of tumors in liver, colon, breast, lung, and pancreas [35]. Recently, we have demonstrated that c-Src phosphorylates tyrosine residues of human EYA1 and EYA3 to control their nuclear and cytoskeletal localization [30]. We have also found that EYA1 and EYA3 are capable of autodephosphorylation [30].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations